A BIBLIOMETRIC REVIEW OF CRITICAL THINKING IN K–12 EDUCATION RESEARCH LITERATURE (1973–2023) - Mahardika, Dimas Pandu; Sukarmin, Sukarmin; Rahmasari, Lita (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Critical thinking is one of the competencies that is of concern for the success of K–12 education. Progressively, the development of critical thinking research and K–12 education has increased rapidly in recent years. This study conducted a bibliometric review of critical thinking in K–12 education to undertake a tracking of the research trends over the last 50 years, using metadata obtained from the Scopus database. The main findings of the study are: (1) critical thinking in K–12 education has increased exponentially since the 2000s; (2) even though the United States is the centre of distribution of this research, the institution with the largest number of publications is in Indonesia..; (3) the field of critical thinking encompasses a wealth of constantly evolving research topics, and the research topic of critical thinking skills has gained significant popularity. This study has significant ramifications and could be used as a point of reference for future research.